2021
DOI: 10.3390/ijerph181910088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends of Physical Activity in Thai Children and Young People: Pooled Panel Data Analysis from Thailand’s Surveillance on Physical Activity 2012–2020

Abstract: This study aims to describe the level and trends of physical activity (PA) in Thai children and young people and examine PA changes during transitional periods. Employing nine rounds of Thailand’s Surveillance on Physical Activity (SPA) 2012–2020, this study pooled three sets of data and included children and young people aged 6–17 years in the analysis: 1595 in SPA2012–2016, 1287 in SPA2017–2019, and 853 persons in SPA2020. Face-to-face interviews were conducted in five regions, 13 provinces, and 36 villages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Similarly, Gropper et al [ 15 ] found an average weight gain of 3.0 kg over the college period [ 15 ]. Moreover, a high percentage of university students in the United States and other countries do not meet PA and dietary recommendations of a healthy lifestyle [ 16 , 17 ]. Wang [ 18 ] found that, in a sample of 4000 college students in China, more than 75 percent did not follow the recommended amounts of PA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gropper et al [ 15 ] found an average weight gain of 3.0 kg over the college period [ 15 ]. Moreover, a high percentage of university students in the United States and other countries do not meet PA and dietary recommendations of a healthy lifestyle [ 16 , 17 ]. Wang [ 18 ] found that, in a sample of 4000 college students in China, more than 75 percent did not follow the recommended amounts of PA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the transition from daily classroom instruction to various remote learning methods, youth experienced adverse changes to their daily routines. In the pre-COVID-19 period, Thai students accumulated an average of 53 min of MVPA ( 26 ). However, only 47 min of MVPA was recorded during the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“… 27 , 37 However, it should be noted that, even before the pandemic, adolescents were considered the least active group of the population. 38 Working from home also reduced PA opportunities for working-age young adults who usually collected most of their daily PA minutes from work- and commuter-related activities. 39 Failure to adjust to the “new normal” has further delayed the recovery of these 2 groups.…”
Section: Discussionmentioning
confidence: 99%